Improving Student Ability in Collaborative Problem Solving (CPS) Using the Power of Two (TPOT) Model - Muhammad Sarlin; Arfan Arsyad; Ikhfan Haris (Nusantara Science and Technology Proceedings, 2022)
The purpose of this study was to find whether the Power of Two (TPOT) strategy was effective or not to improve the ability of students in solving a problem collaboratively. The research uses action research within a pre-experimental design. The study involved an experimental group consisting of 36 students in grade VIII of Junior High School in Gorontalo District, Gorontalo Province, Indonesia. This study employed a collaborative classroom action study method conducted in two cycles, using instruments in the form of observation sheets and questionnaires on the ability of students to collaborate in solving a problem by applying the TPOT model. The results of this study reveal that the observation of students' ability to solve problems collaboratively increased from the first cycle to 74.58% and in the second cycle to 84.45%. The application of the TPOT model was able to improve the ability of students from the initial assessment in the first cycle 69 % to the second cycle 86 % and the questionnaire on students' ability to collaborate to solve problems greater than before Cycle I, 75.56 % and Cycle II 88.89 %. The research concluded that the TPOT model can improve students' ability in Collaborative Problem Solving (CPS). Research recommendations necessitate using the TPOT model as one of the strategies to improve students' ability to collaborate in problem solving.